1990
DOI: 10.1002/pd.1970100510
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis and postnatal follow‐up of a child with two de novo unrelated balanced reciprocal translocations

Abstract: Two unrelated, apparently balanced, reciprocal translocations involving chromosomes 3 and 17, and 10 and 15 were found in cultured amniotic fluid cells from a 41-year-old 10-gravida. Chromosome analysis of peripheral blood lymphocytes of both parents revealed normal karyotypes. Post-partum examination of lymphocyte cultures from the proband confirmed the chromosome rearrangements. The child showed normal development during follow-up examinations up to the age of 4 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(21 reference statements)
0
6
0
1
Order By: Relevance
“…Of the 11 previous reports of de novo balanced CCRs identified prenatally none involved mosaicism and only on two did ultrasound indicate a likely abnormal outcome when IUGR was detected prenatally (Kim et al, 1986;Cotter et al, 1996). Follow-up of the remaining cases postnatally revealed that three were dysmorphic with developmental delay (Ruiz et al, 1996;Bogart et al, 1986); one had speech delay (Stoll et al, 1979) but five were clinically normal (Kohler et al, 1986;Batista et al, 1993;Sikkema-Raddatz et al, 1995;Pruggmayer et al, 1990) (Table 1). In two large surveys additional CCRs were noted but no follow-up details were given (Hook and Cross 1987;Warburton, 1991).…”
Section: Discussionmentioning
confidence: 89%
“…Of the 11 previous reports of de novo balanced CCRs identified prenatally none involved mosaicism and only on two did ultrasound indicate a likely abnormal outcome when IUGR was detected prenatally (Kim et al, 1986;Cotter et al, 1996). Follow-up of the remaining cases postnatally revealed that three were dysmorphic with developmental delay (Ruiz et al, 1996;Bogart et al, 1986); one had speech delay (Stoll et al, 1979) but five were clinically normal (Kohler et al, 1986;Batista et al, 1993;Sikkema-Raddatz et al, 1995;Pruggmayer et al, 1990) (Table 1). In two large surveys additional CCRs were noted but no follow-up details were given (Hook and Cross 1987;Warburton, 1991).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, only the remaining two confirmed cases had phenotypes probably associated with the BRTM [Saura et al, 1987;Aughton et al, 1993]. This could be due to gene disruption, gene position effect, submicroscopic loss, or duplication of euchromatin [Pruggemayer et al, 1990].…”
Section: Discussionmentioning
confidence: 95%
“…There have been only eight previous reports of de novo MCRs or CCRs identified a t prenatal diagnosis (Table I). Of the five liveborns, three were reported to be normal [Kohler et al, 1986;Pruggmayer et al, 1990;Sikkema-Raddatz et al, 19951. The case reported by Bogart et al [1986] appeared normal a t 2 YZ years but had speech delay, while the case reported by Stoll et al [1979] was developmentally delayed and dysmorphic.…”
Section: Discussionmentioning
confidence: 98%